Application of a correction factor in the estimate of the trapping success of pest rodents - Javier Monge; Carol Sánchez (Agronomía Costarricense, 2015)
The effect of adding a correction factor in the formula used to estimate the trapping success of rodents, as well as the duration of the period of sampling (1, 2 or 3 days) and the effect of considering rodents captured as a single species or by differentiating them, were examined. The correction factor involved considering those traps with poor performance as the average value (traps activated without bait, disabled with or without bait, catch of a species different from that of interest and traps lost or removed). Estimated trapping success was 3.67% and 3.85%, according to the traditional formula and the corrected version, respectively, in one of the study sites where the predominant species was Sigmodon hirsutus, and 3.20 and 3.89% in another site, with Mus musculus as the predominant species. No significant differences were found in the estimate of trapping success with the use of one or the other formula, in both study sites. Sampling for just one day was enough to estimate the trapping success (4.14%), since there were no significant differences compared to 2 days of sampling (4.04%) or 3 days (3.67%). Also, there were no significant differences when comparing the method to identify each species of rodents (3.67%) with the method to consider all individuals captured as a single species (3.88%). Our results correspond to a situation with a relatively low capture of rodents, as well as when there is a predominant species present, thus it would be convenient to corroborate these results in a situation of greater abundance of rodents, as would be the case when they reach the condition of plague.